2021
DOI: 10.1186/s12870-021-03016-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic survey, structural classification and expression analysis of C2H2-type zinc finger factor in wheat (Triticum aestivum L.)

Abstract: Background The C2H2-type zinc finger proteins (C2H2-ZFPs) are one of major classes of transcription factors that play important roles in plant growth, development and stress responses. Limit information about the C2H2-ZF genes hinders the molecular breeding in bread wheat (Triticum aestivum). Results In this study, 457 C2H2-ZFP proteins (including 253 splice variants), which contain four types of conserved domain (named Q, M, Z, and D), could be fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…Previous reports indicate that they play an important role in cucumber, Arabidopsis , wheat, and tomato [ 39 , 40 , 41 , 42 ]. Therefore, many researchers have tried to perform genome-wide analysis on C2H2-ZFP s in various species, such as tomato, wheat, grape, and oyster mushroom [ 43 , 44 , 45 , 46 ], but little is known about sorghum C2H2-ZFP proteins. In this study, we carried out a genome-wide study of the S. bicolor C2H2-ZFP family and identified a total of 145 SbC2H2-ZFP members.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicate that they play an important role in cucumber, Arabidopsis , wheat, and tomato [ 39 , 40 , 41 , 42 ]. Therefore, many researchers have tried to perform genome-wide analysis on C2H2-ZFP s in various species, such as tomato, wheat, grape, and oyster mushroom [ 43 , 44 , 45 , 46 ], but little is known about sorghum C2H2-ZFP proteins. In this study, we carried out a genome-wide study of the S. bicolor C2H2-ZFP family and identified a total of 145 SbC2H2-ZFP members.…”
Section: Discussionmentioning
confidence: 99%
“…Q-Type ZFPs are a subfamily of C2H2-ZFPs, which play crucial roles in plant response to abiotic stress. Previous studies have identified many Q-type C2H2 ZFPs in plants such as Arabidopsis , rice, wheat, poplar, and potato [ 9 , 10 , 36 , 37 , 38 ]. However, there have been few studies on the molecular function of MsZFP s under abiotic stress conditions in alfalfa.…”
Section: Discussionmentioning
confidence: 99%
“…The LD decay analysis was calculated for the whole genomes using the full matrix and sliding window options in Tassel v5.0 (Breseghello and Sorrells, 2006). The results of LD decay, population analysis, PCA, and NJ-tree analysis for the 251 spring wheat accessions have been reported by Li et al (2021). The multi-environment phenotypic data were analyzed by a one-stage approach as y 1 n μ + Xg + Ze + v + ε, where y is the n-dimensional multi-environment phenotypic records, n is the number of multi-environment phenotypic records, 1 n is an n-dimensional vector of ones, μ is the intercept, g and e are the vector of genetic and environment effects, respectively, v is the vector of genotype-by-environment interaction effects, X and Z are the design matrices of g and e, respectively, and ε is the random residuals.…”
Section: Plant Materials and Field Trialsmentioning
confidence: 99%
“…Genotyping, population structure, and linkage disequilibrium decay analysis Totally, 52,503 polymorphic SNPs after filtering (MAF <0.05, missing rate >0.1) were conducted for further GWAS (Li et al, 2021). Among the SNP markers, 18323, 18691, and 15489 were from A, B, and D genomes, respectively, with an average marker density of 0.273 Mb per marker.…”
Section: Phenotypic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation